Long-lasting fitness consequences of prenatal sex ratio in a viviparous lizard. - Uller, T; Massot, M; Richard, M; Lecomte, J; Clobert, J (2004)
Maternal effects and early environmental conditions are important in shaping offspring developmental trajectories. For example, in laboratory mammals, the sex ratio during gestation has been shown to influence fitness-related traits via hormonal interaction between fetuses. Such effects have the potential to shape, or constrain, many important aspects of the organism's life, but their generality and importance in natural populations remain unknown. Using long-term data in a viviparous lizard, Lacerta vivipara, we investigated the relationship between prenatal sex ratio and offspring growth, survival, and reproductive traits as adults. Our results show that females from male-biased clutches grow faster, mature earlier, but have lower fecundity than females from female-biased clutches. Furthermore, male reproduction was also affected by the sex ratio during embryonic development, with males from male-biased clutches being more likely to successfully reproduce at age one than males from female-biased clutches. Thus, the sex ratio experienced during gestation can have profound and long-lasting effects on fitness in natural populations of viviparous animals, with important implications for life-history evolution and sex allocation.